Le déploiement des réseaux communautaires sans fil (MESH) - François Huguet (Netcom)
The “infrastructural mediation” concept, understood as the activity that promotes and develops the production of citizen-driven technical infrastructures, currently seems able to inform a number of existing techno-civic urban practices which are related to the commons. This article specifies the notion and articulates it with those of agency, inverse infrastructure and socio-technical vulnerability. To do so, it explores its implications through an emerging network technology analysis (Commotion MESH wireless community networks), its actants and the community practices that it reveals in the city of Detroit (USA).